Section 5: Patient Safety and Quality Assurance 2018
DOI: 10.1136/ejhpharm-2018-eahpconf.371
|View full text |Cite
|
Sign up to set email alerts
|

5PSQ-017 Safety of intravenous ferric carboxymaltose in treatment of iron deficiency in children under 2 years with intestinal failure

Abstract: BackgroundChildren with intestinal failure (IF) are dependent on parenteral nutrition (PN) for normal growth and development. In our practice, individualised PN contain iron-free paediatric trace element mixtures due to the risk of compatibility problems. Children with IF are thus at risk of developing iron deficiency (ID). Furthermore, oral/enteral iron supplementation (IS) is avoided in children with IF because of the reduced absorptive capacity and risk of side-effects. Intravenous (IV) IS with ferric carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Findings on the efficacy of FCM in children and/or adolescents were reported in 27 of the 33 publications (Table 1 ) [ 21 28 , 30 33 , 36 – 44 , 46 48 , 50 , 51 , 53 ]. In 26 of the 27 publications that included efficacy results, FCM treatment (in most cases a single dose) was associated with improvement in anaemia and/or different iron status parameters, including improvements in levels of haemoglobin (22 publications), ferritin (12 publications), mean corpuscular volume (10 publications), iron (six publications) and transferrin saturation (five publications) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings on the efficacy of FCM in children and/or adolescents were reported in 27 of the 33 publications (Table 1 ) [ 21 28 , 30 33 , 36 – 44 , 46 48 , 50 , 51 , 53 ]. In 26 of the 27 publications that included efficacy results, FCM treatment (in most cases a single dose) was associated with improvement in anaemia and/or different iron status parameters, including improvements in levels of haemoglobin (22 publications), ferritin (12 publications), mean corpuscular volume (10 publications), iron (six publications) and transferrin saturation (five publications) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study of 51 children reported improvements in haemoglobin, iron and TSAT following FCM treatment [ 39 ]. The use of FCM has also been reviewed retrospectively in children < 2 years old with intestinal failure and ID [ 21 ]. All 14 children who received one or two doses of FCM responded with complete or partial normalisation of markers for ID.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in adult and pediatric patients with inflammatory bowel disease demonstrate significant, longer lasting improvements in anemia at a few months after administration of FCM when compared with other iron formulations. There are no longer term studies in pediatric patients, as all studies followed patients for around 12 weeks 10,12,16–19 . There is a single study in pediatric patients with IF <2 years of age, but no longitudinal follow‐up 19 .…”
Section: Introductionmentioning
confidence: 99%
“…There are no longer term studies in pediatric patients, as all studies followed patients for around 12 weeks. 10,12,[16][17][18][19] There is a single study in pediatric patients with IF <2 years of age, but no longitudinal follow-up. 19 Currently, there are no longitudinal studies guiding the potential use of FCM in pediatric patients with IF who typically require longterm iron repletion.…”
Section: Introductionmentioning
confidence: 99%